In vitro antioxidant and antimicrobial activity of Cannabis sativa L. cv ʻFutura 75ʼ essential oil. Issue 24 (17th December 2021) - Pellegrini, Marika; Palmieri, Sara; Ricci, Antonella; Serio, Annalisa; Paparella, Antonello; Lo Sterzo, Claudio
Abstract: In the present work, Cannabis sativa L. cv Futura 75 inflorescences, cultivated in the Abruzzo territory, were characterized for their volatile fraction through SPME-GC-MS. In addition, the essential oil extracted from these inflorescences was investigated for the antioxidant potentialities and for the terpenic profile. The antibacterial activity of hemp essential oil (HEO) against some pathogenic and spoilage microorganisms isolated from food was also evaluated by determining the minimal inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). The results showed significant antioxidant capacity (DPPH: 63.38 ± 0.08 mg TE/g HEO; FRAP: 438.52 ± 6.92 mg TE/g HEO) alongside good antibacterial activity against Gram-positive bacteria such as S. aureus and L. monocytogenes (MIC 1.25-5 µL/mL). The results obtained suggest that hemp essential oil can inhibit or reduce bacterial growth, also exerting antioxidant activity, and therefore it can find an advantageous application in the food processing field. Graphical Abstract: UF0001